Selection of Natural Fruit Ingredients for the Production of Wine Cocktails with High Organoleptic Properties - Simonyan, N. R.; Solomonyan, A․ K․ (ՀԱԱՀ հիմնադրամ)
The aim of the research is to identify and select natural fruit ingredients for the production of wine cocktails with high organoleptic properties via investigating the chemical and organoleptic indices of the produced cocktails. Dried apricots and kumquat fruits have been selected as fruit ingredients. They have been mixed with the dry white wine materials with the doses of 10 g/dm3 and 20 g/dm3 respectively.
Keywords: Food Science and Technology